Predictors of loneliness among students and nuns in Angola and Portugal - Félix Neto (2003)
The authors conducted 2 studies to examine the relationship between loneliness and psychosocial variables among people from Angola and Portugal. In the 1st study, the participants were 129 college students from Angola and 122 from Portugal, and in the 2nd study participants were 105 nuns from Angola and 74 from Portugal. The following instruments were administered to all participants in both studies: the Revised UCLA Loneliness Scale (D. Russell, L. Peplau, & C. Cutrona, 1980), the Neuroticism Scale (J. Barros, 1999), the Optimism Scale (J. Barros, 1998), and the Satisfaction With Life Scale (E. Diener, R. Emmons, R. Larsen, & S. Griffin, 1985). Ethnic differences were found in loneliness. The Angolan participants recorded higher scores for loneliness than did the Portuguese participants. For both samples the most prominent predictors of loneliness were neuroticism and dissatisfaction with life.